Existence of Pseudo Almost Automorphic Solutions for the Heat Equation with Sp-Pseudo Almost Automorphic Coefficients. (17th August 2009) - Diagana, Toka; Agarwal, Ravi P.
Abstract : We obtain the existence of pseudo almost automorphic solutions to theN -dimensional heat equation withS p -pseudo almost automorphic coefficients.